Behavioral assessment and Activity Pattern of Two-toed Ostrich (Struthio camelus) in captive environment - Sidra, Safdar; Shabbir, Sana; Zafar, Saima; Khaliq, Aiza; Arqam, Ali (Journal of Basic and Emerging Sciences, 2024)
Captive conditions can result in deviation in behaviour and activities of the animals from the wild environment. It is necessary to regularly monitor the activities and behavioral pattern in captive animals to record any changes from normal for the well-being of the animals. Two-toed ostrich (Struthio camelus) is a large flightless bird endemic to the Ethiopian region. It is being farmed in many countries due to its low fat content and favorable fatty acid profile as compared to beef. The behaviour of ostrich is not well studied in wild or captivity so the current study was designed to observe and compare the behavioral trends in ostrich in three different captive environments i.e. Lahore Zoo (a highly urbanized locality), Captive Breeding and Research Center, UVAS (a semi-urban site), and Rachna Wildlife Park (a semi-captive environment). While there was no significant difference to be observed in activity pattern of ostrich in semi-urban environment and highly urbanized settings, time budget for various activities differed with the time of the day. Seasonal impact upon the general behaviour was also found to be pronounced.